Critical Evaluation of Road Bends on User Safety: A Systematic Literature Review Study - Wahyudi, Fahmi Faizal; Herdiawan, Vickry Afrizal; Nurrohman, Muhammad Ridwan; Juliar, Eka; Handayani, Susanty (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Road curves often become vulnerable to traffic accidents, which remain a significant worldwide issue. This study provides an essential analysis of the effects of road geometry on curves on user safety. The main objective of this research is to identify the relationship between the features of curve infrastructure, such as radius, superelevation, and lane width, and the traffic accident rate. Accident data from various road segments in Indonesia was thoroughly analyzed. Special emphasis is placed on the types of accidents, their severity levels, and the contributing factors to these accidents. Studies show that curves with suboptimal designs, such as small radii or lack of superelevation, significantly increase the risk of accidents. Additionally, the consistency of geometric design and the visual perception of curves significantly affect the safety of drivers and other road users. This study highlights the importance of using a comprehensive approach in the planning and designing road curves to enhance overall transportation safety. The proposed recommendations include stricter design guidelines, improved maintenance, and better instructions for road users to reduce the risk of curve accidents.